Răspuns:
Explicație pas cu pas:
A(a; -a)
f(a) = -a
2a - 1 = -a
2a + a = 1
3a = 1
a = 1/3
A(1/3; -1/3)
B(-b; b)
f(-b) = b
-2b - 1 = b
b + 2b = -1
3b = -1
b = -1/3
B(1/3; -1/3)
Raspuns a) punctul este (1/3; -1/3)
_________________
f(1) = 2 - 1 = 1
f(2) = 4 - 1 = 3
f(3) = 6 - 1 = 5
............
f(20) = 40 - 1 = 39
S = 1 + 3 + 5 + ...+ 39
progresie aritmetica cu ratia 2
an = a1 + (n - 1)*r
39 = 1 + (n - 1)*2 = 1 + 2n - 2 = 2n - 1
2n = 39 + 1 = 40
n = 40 : 2 = 20
Sn = n*(a1 + an)/2
S = 20*(1 + 39)/2 = 20*40/2 = 10*40 = 400